KETERAMPILAN LITERASI DIGITAL DALAM PEMANFAATAN BIG DATA DEMI TERWUJUDNYA MASYARAKAT PENGETAHUAN - Tansah Rahmatullah, Tansah Rahmatullah (PT. Solusi Komunikasi Terapan, 2024)
While the skills to use digital media, data sets, and the internet for specific purposes are undoubtedly important skills, citizens in today’s knowledge society need more than just skills. They must understand and critically reflect on the widespread collection of their personal data on the internet and the potential risks and implications that will arise with big data practices. This article discusses the insights into digital skills needed in utilizing big data to realize a knowledge society, which is not only skilled, but also has awareness of open data information behavior, so that society becomes wiser, and the potential risks and threats that lurk can be minimized or even avoided. This study uses a qualitative research methodology that is presented descriptively and contains quotes from data to describe what a particular situation or worldview is like in narrative form. Qualitative research is conducted through the presentation of opinions or understandings of experts on the observed phenomena. The type of research used in this article is a type of library research, where the author collects data in the form of books, manuscripts, scientific articles, reports, survey results, websites or magazines that are relevant to the object of research. In the perspective of big data, and because of the interest in realizing a knowledge society, social change is needed in society specifically in the form of a shift from an information society based on a knowledge economy to a society based on knowledge. A knowledge society is a society that produces, processes, shares, and makes knowledge that can be used to improve human conditions available to all its members. The challenge of big data digital literacy skills in realizing a knowledge society lies in the effort to form human competence and ability to learn from a number of data that significantly exceeds human cognitive capacity. The competence and ability in question are a combination of various skills to learn from data developed by all forms of literacy, which need to be supported by additional expertise, namely knowledge, skills and experience.